2006
DOI: 10.1103/physrevb.73.165317
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence investigation of the carrier recombination processes in ZnO quantum dots and nanocrystals

Abstract: The carrier recombination processes in ZnO quantum dots ͑ϳ4 nm in diameter͒, ZnO nanocrystals ͑ϳ20 nm in diameter͒ and bulk ZnO crystal have been studied using photoluminescence ͑PL͒ spectroscopy in the temperature range from 8.5 to 300 K. The obtained experimental data suggest that the ultraviolet PL in ZnO quantum dots originates from recombination of the acceptor-bound excitons for all temperatures. In the larger size ZnO nanocrystals, the recombination of the acceptor-bound excitons is the dominant contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
243
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(276 citation statements)
references
References 46 publications
27
243
6
Order By: Relevance
“…where L is the excitation intensity and k is the power factor [49]. The underlying recombination process for 1 < k < 2 is known to be excitonic, whereas for k < 1 either a donor state (D-h), an acceptor state (e-A) or both states (donor-acceptor pair transition) are involved.…”
Section: Discussionmentioning
confidence: 99%
“…where L is the excitation intensity and k is the power factor [49]. The underlying recombination process for 1 < k < 2 is known to be excitonic, whereas for k < 1 either a donor state (D-h), an acceptor state (e-A) or both states (donor-acceptor pair transition) are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Several emission bands, including band edge UV emission at 400 nm ($3.10 eV) and defect related violet emission at 420 nm ($2.95 eV), blue-green emission at 482 nm ($2.57 eV) and green emission at 524 nm ($2.36 eV) were observed. In PL spectrum of ZnO band at 400 nm, could be attributed to free exciton recombination through exciton-exciton collisions, [23] corresponding to the near-band-gap emission (NBE), which corresponds to an energy gap of 3.10 eV.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The origin of the A-line emission is currently under discussion. Possible assignments of the A-line include: neutral excitons bound to nitrogen impurities (Look et al, 2002;Yang et al, 2006), donor-acceptor pair recombination , free-to neutral-acceptor transitions (Cao et al, 2007), two-electron transition of exciton bound to neutral donor (Studenikin et al, 2000), the first longitudinal optical (LO) phonon replica of free excitons (Hirai et al, 2008) or excitons bound to surface or structural defects ( Fallert et al, 2007;Fonoberov et al, 2006;He et al, 2007;Meyer et al, 2004;Teke et al, 2004). Recently, on a basis of cathodoluminescence measurements, it was suggested that this line is composed of two overlapped bands related to point defects and the first LO phonon replica of the free exciton (Mass et al, 2008).…”
Section: Introductionmentioning
confidence: 99%